Small cell carcinoma of the oesophagus: report of three cases and review of published cases. Issue 9 (September 1989) - Eccles, D M; Allan, S G; Sang, C T; Cornbleet, M A
Abstract : Small cell carcinoma of the oesophagus is a rare tumour with a poor prognosis. This report presents evidence favouring chemotherapy as the primary treatment.